2020
DOI: 10.1002/osp4.417
|View full text |Cite
|
Sign up to set email alerts
|

Differences in brain structure and function in children with the FTO obesity‐risk allele

Abstract: Objective: Noncoding alleles of the fat mass and obesity-associated (FTO) gene have been associated with obesity risk, yet the underlying mechanisms remain unknown. Risk allele carriers show alterations in brain structure and function, but previous studies have not disassociated the effects of genotype from those of body mass index (BMI). Methods: Differences in brain structure and function were examined in children without obesity grouped by their number of copies (0,1,2) of the FTO obesity-risk single-nucleo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 56 publications
0
11
0
Order By: Relevance
“…Firstly, we tried to verify the previously reported variants in our discovery cohort. We noticed that the inconsistent associations of FTO SNPs with regional brain volumes were reported in adolescents or children ( Rapuano et al, 2017 , Lugo‐Candelas et al, 2020 ), while the consistent association was reported in elder people ( Ho et al, 2010 ). We speculate that the effect of FTO gene on regional brain volumes may interact with age.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Firstly, we tried to verify the previously reported variants in our discovery cohort. We noticed that the inconsistent associations of FTO SNPs with regional brain volumes were reported in adolescents or children ( Rapuano et al, 2017 , Lugo‐Candelas et al, 2020 ), while the consistent association was reported in elder people ( Ho et al, 2010 ). We speculate that the effect of FTO gene on regional brain volumes may interact with age.…”
Section: Discussionmentioning
confidence: 79%
“…Other SNPs of the FTO gene, such as rs1421085, rs9930333, rs3751812, have also been reported. FTO rs1421085-C was associated with the increased grey matter volumes of the right middle temporal gyrus, parahippocampal gyrus, lateral occipital cortex ( Lugo‐Candelas et al, 2020 ), while FTO rs3751812-T was associated with the reduced volume of occipital lobe ( Ho et al, 2010 ). FTO rs9930333-G was not associated with ventricular cerebrospinal fluid volume ( Melka et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Lower volume of the frontal and occipital lobes has been observed in healthy young (average age of 26 years) and elderly adults homozygous for the rs9939609 risk allele or proxies 76,77 . Lower grey matter in individuals carriers for FTO risk alleles has also been reported in other brain regions such as those related to reward, 76,78 and increased grey and white matter in the cerebellum 79 has been reported in individuals homozygous for the rs1421085 risk allele. Lastly, altered activity associated with FTO risk alleles has been reported in brain areas of food reward, termination of eating, and visual aspects of food perception, in agreement with the hypothesis that feeding behavior is modulated by FTO SNPs 63,71,76,80 …”
Section: Human Functional Studiesmentioning
confidence: 96%
“…An experimental study observing brain morphology changes following bariatric surgery found an effect of childhood obesity on cortical thickness (12). Genetically informed analyses revealed directional effects from polygenic scores for BMI to ADHD, heavy smoking (42), and overeating (43), as well as cortical volume (44). Schizophrenia and anorexia nervosa genetic propensity were identified to predict childhood obesity (42).…”
Section: Introductionmentioning
confidence: 99%
“…Genetically informed analyses revealed directional effects from polygenic scores for BMI to ADHD (Hübel et al, 2019) and overeating (Herle et al, 2021), as well as cortical volume (Lugo-Candelas et al, 2020). Anorexia nervosa genetic propensity was identified to predict childhood obesity (Hübel et al, 2019).…”
Section: Introductionmentioning
confidence: 99%